2007
DOI: 10.1007/s00404-007-0370-0
|View full text |Cite
|
Sign up to set email alerts
|

Anthropometric measurements in the diagnosis of pelvic size: an analysis of maternal height and shoe size and computed tomography pelvimetric data

Abstract: Measurements of maternal height, shoe size and weight at the last clinic visit are not useful for the identification of women with inadequate pelvis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 20 publications
2
17
0
Order By: Relevance
“…Unfortunately, the risk-approach to reducing maternal mortality and morbidity has not worked in practice because the vast majority of life-threatening obstetric complications arise unexpectedly and cannot be predicted in advance [13-15]. In spite of decades of effort using both high- and low-technology approaches, there are still no screening tools with adequate sensitivity and specificity for routine clinical use that will predict which women will develop obstructed labor in advance of labor itself [16-20]. The most reliable predictor of obstetric outcome is past obstetric history, a fact that is particularly unhelpful for evaluating potential complications during a woman’s first pregnancy [21].…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, the risk-approach to reducing maternal mortality and morbidity has not worked in practice because the vast majority of life-threatening obstetric complications arise unexpectedly and cannot be predicted in advance [13-15]. In spite of decades of effort using both high- and low-technology approaches, there are still no screening tools with adequate sensitivity and specificity for routine clinical use that will predict which women will develop obstructed labor in advance of labor itself [16-20]. The most reliable predictor of obstetric outcome is past obstetric history, a fact that is particularly unhelpful for evaluating potential complications during a woman’s first pregnancy [21].…”
Section: Discussionmentioning
confidence: 99%
“…Maternal obesity has also been suggested as a risk factor for CPD [7,24,25]. Rickets is known to be a cause for small or distorted pelvis [20,23]. One study of an immigrant population of women from countries with high rates of malnutrition to the USA, reports that this population had higher rates of CPD following their immigration, probably due to malnutrition during puberty [26].…”
Section: Introductionmentioning
confidence: 97%
“…A meta-analysis investigating the association between short stature and CPD revealed that one of Wve short stature women were referred to caesarian section (CD) for having small pelvises [22]. Nevertheless, short stature is not necessarily an indication for a small size pelvis [23]. Maternal obesity has also been suggested as a risk factor for CPD [7,24,25].…”
Section: Introductionmentioning
confidence: 98%
“…Hormonal changes in women may lead to loosening ligaments, and have been suggested to cause an increase in ligamentous tears in female athletes of reproductive age. The increase in specific hormone levels, including Relxain, Progesterone, and Estradiol, which contribute to general ligamentous laxity, may also contribute to arch collapse during pregnancy. It is well known that pregnant and nulliparous women are exposed to different concentrations of hormones, as age, age at menarche, and age at first live birth are used in the GAIL breast cancer calculation.…”
Section: Introductionmentioning
confidence: 99%